Telur EMAS (Enak, Masir, Aman, Sehat) sebagai Telur Asin Rendah Kolesterol - Firdaus, Faza Akbar; Alfian, Romi; Sya’Roni, Mochammad Imam (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The purpose of production Telur EMAS (Enak, Masir, Aman, Sehat) sebagai Telur Asin Rendah Kolesterol was to create product salt egg with lower cholesterol than salt egg in traditional market and the same products that were already exist. Telur EMAS was adding garlic when the production, that as known proven to make cholesterol become lower. That we realize the cholesterol of salt egg were so high 2.188mg/100gram, the requirement of the body are 1.100mg/day. That was so unhealthy, and another purpose of the writer was increase good food in mass. The method to promoting Telur EMAS were concentrate in tourists object in Malang city and Batu city, also the center of gift.Â Keywords : Salt Egg, Lower Cholesterol, Garlic